Pengaruh Persepsi Dukungan Organisasi, Stres Kerja, Dan Kepuasan Kerja Terhadap Komitmen Afektif Karyawan Perusahaan Produsen Air Kemasan Cam Di Bandung - Tieka Trikartika Gustyana; Arif Partono Prasetio; Alya Rysda Ramadhanty; Nabila Azahra (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2018)
Employees become an important factor in the success of the organization. They have impact on almost every business activity. Therefore company needs to manage their human resources in order to get highest performance. Many human resources practices implemented to achieve such result. One thing that indicate a positive result is the level of employee commitment toward the organization. Committed employees will contribute more. Affective commitment is the highest level of commitment because this emerge from within the employee's feelings. This study discusses the effect of perceived organizational support (POS), stress, and job satisfaction on employee’s affective commitment. The research was conducted in the drinking water company in Bandung using 85 participants. The analysis technique used is partial correlation analysis to identify the relationship between variables and also identify control variables that affect each relationship. Furthermore, mediation analysis is used to determine whether stress and job satisfaction have a mediating role in the relationship of POS influence to affective commitment. The results showed that POS had no significant effect on affective commitment. Furthermore, stress does not have the role of mediation either partially or simultaneously with job satisfaction. While job satisfaction has a partial mediation role in the relationship of influence between POS and affective commitment.